2017
DOI: 10.1038/s41598-017-12098-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep restriction on empathy for pain: An fMRI study in younger and older adults

Abstract: Age and sleep both affect emotional functioning. Since sleep patterns change over the lifespan, we investigated the effects of short sleep and age on empathic responses. In a randomized cross-over experimental design, healthy young and older volunteers (n = 47 aged 20–30 years and n = 39 aged 65–75 years) underwent functional magnetic resonance imaging (fMRI) after normal sleep or night sleep restricted to 3 hours. During fMRI, participants viewed pictures of needles pricking a hand (pain) or Q-tips touching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 44 publications
8
44
1
Order By: Relevance
“…However, our results agree with previous results from SB2 (46) using partial sleep deprivation, as we did not use KSS in the same way as in that study. It also agrees with the work by Wong et al (47) that showed that GSV decreases with caffeine intake and increased vigilance, and with the findings by Fukunuga et al (48) that GSV increases during sleep.…”
Section: Recapitulation and Discussionsupporting
confidence: 92%
“…However, our results agree with previous results from SB2 (46) using partial sleep deprivation, as we did not use KSS in the same way as in that study. It also agrees with the work by Wong et al (47) that showed that GSV decreases with caffeine intake and increased vigilance, and with the findings by Fukunuga et al (48) that GSV increases during sleep.…”
Section: Recapitulation and Discussionsupporting
confidence: 92%
“…A more detailed report of the polysomnography results can be found in (35). Because the drop-outs in this publication differ compared to previous publications from the same experiment the numbers are slightly different compared to (28,3436).…”
Section: Resultsmentioning
confidence: 76%
“…One such difference that was aimed to be addressed in this study was age. Some of our previous work indicates that the effect of sleep restriction on both empathy (34) and mood (Schwarz submitted) is different in older age. This study did not specifically analyze the interaction between sleep restriction and age, but the results on ratings of success and unpleasantness are in line with a potential reduced sensitivity to sleep loss in older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was limited by a small sample size and the lack of established outcome measures that differentiate between negative and positive dimensions of affect. Using an empathy for pain paradigm, our recent findings indicate that the effect of partial sleep deprivation in older adults is opposite to that in younger adults (Tamm et al., ). This study focused specifically on empathy, and not on more general aspects of emotion, but nevertheless further underscores the need to study sleep manipulations in different age groups.…”
Section: Introductionmentioning
confidence: 83%